Pemurnian Bioetanol Dari Limbah Kulit Kopi Dengan Menggunakan Zeolit Alam dan Batu Gamping - Sri Mutia Heriwati; Zahra Fona; Adriana Adriana (Politeknik Negeri Lhokseumawe, 2021)
In this research, zeolites were used to increase the levels of ethanol distillation process results of laboratory Department of Chemical Engineering Politeknik Negeri Lhokseumawe. Ethanol yield after distillation process only reaches 20.66%, to increase the concentration of ethanol used advanced treatment is by the adsorption method. The results were obtained optimum ethanol concentration, ie 38.67% with a contact time of 8 hours and 80 mesh size. the refractive index and density of 1.33960 and 0.798. bioethanol with 3 g of limestone can eliminate moisture content up to 29.36%; the activation treatment adsorption process of bioethanol with adsorbent zeolite, limestone, and limestone following the zeolite with Freundlich isotherm with adsorption capacity of each 4.5 mg / g; 5.7 mg / g; and 6.4 mg / g.